Applications in basic marketing : - Perreault, William D. (McGraw-Hill/Irwin, 2005)
The book provides a flexible and helpful set of teaching and learning materials. We have included clippings (articles) on a wide variety of topics. The clippings deal with consumer products and business products, goods and services, new developments in marketing as well as traditional issues, and large well-known companies as well as new, small ones. They cover important issues related to marketing strategy planning for both domestic and global markets.